Implementasi Standar Mutu Pendidikan Menurut Rusydi Ahmad Thu'aimah - Fayyad AS, Moh; Muhlis, Achmad (STIT Fatahillah, 2025)
Educational quality standards, as emphasized by Rusydi Ahmad Thu’aimah, stress the comprehensive development of students, encompassing academic, moral, spiritual, social, and managerial aspects. Educational quality is understood as the ability of an institution to foster the potential of students in cognitive, affective, and psychomotor domains, in accordance with Islamic values and societal needs. To realize these quality standards, educational institutions require a relevant curriculum, effective learning, professional educators, a conducive learning environment, and well-directed management. The implementation of educational quality management involves systematic planning, execution, and supervision. Planning includes setting objectives, strategies, needs analysis, and performance indicators, involving all school members to build a shared vision. Implementation is carried out through educational programs that support comprehensive quality achievement, including teacher competency improvement, standardized learning management, and collaboration with the community. Supervision through monitoring, evaluation, and feedback ensures alignment with quality standards and promotes continuous improvement. Thus, educational quality management serves as a strategic mechanism to translate Thu’aimah’s quality standards into practical application, producing students who are knowledgeable, morally upright, and beneficial to society.